Developing a family engagement plan for Native Hawaiian and Pacific Islander STEM students in higher education: A review and critique of the literature. (6th August 2020) - Baker, Jonathan D.; Keahiolalo, RaeDeen M.; Keahi‐Wood, Kahoali'i; Cogbill, Jolene; Naeole, Chrystie; Turner, Helen
Abstract : This paper reviews and critiques the literature on family engagement programmes in higher education, from the perspective of issues that may affect the design of programmes serving Native Hawaiian and Pacific Islander students and their families. While there is compelling research suggesting that increasing students' family members' engagement with higher education will benefit students, it is unclear whether the concept of family engagement as it is conceived in western educational contexts can be universally and unproblematically applied in Pacific contexts. Recommendations for best practices in family engagement programme design highlight communication efforts with parents that can be characterised as fundraising and 'friendraising', but do not address issues specific to the experiences of under‐represented groups in higher education. Drawing on the literature and experiences of indigenous and other under‐represented students, and incorporating insights from literature on decolonising methodologies, we present considerations for authentic and culturally responsive family engagement for Native Hawaiian and Pacific Islander students, families and communities.